Multi-dimensional review of Paraguay. Volume 3, From analysis to action - Organisation for Economic Co-operation and Development. Development Centre (OECD development pathways, ISSN 2308-734X, 2019)
Summary.
Keywords: taloudellinen kehitys : Paraguay; talouskasvu : Paraguay; yhdenvertaisuus : Paraguay; elinolot : Paraguay; terveydenhuolto : Paraguay; sosiaaliturva : Paraguay; koulutus : Paraguay